The Effect of Different Suture Materials on Achilles Tendon Metabolism: A Preliminary in vivo Study of mRNA levels in Rabbits - YILMAZ GÖLER, AYŞE MİNE (EDRA SPA, 2019)
Backround. Different suture materials are preferable for the repair of Achilles tendon ruptures. The effect of the sutures on the biological level on a repair scenario is still tentative. The purpose of this study is to show the effects of Vicryl (R), Ethibond (R) and PDS (R) II on Achilles tendons at mRNA levels. Methods. 36 Achilles tendons of 18 White New Zealand Rabbit were divided into four groups (n:9). Acute tendon rupture model was created and three groups were repaired with each of the aforementioned sutures (fourth was the control group). At day twelve, mRNA was isolated from each tendon, and expression levels of Collagen (COL) 1A2, COL3A1, Decorin, Matrix Metalloproteinase (MMP) 13 and Interleukin (IL) 1 beta were measured quantitatively and compared. Results. Tendons repaired with PDS (R) II showed high COL1A2, COL3A1 and decorin expression levels (p<0.05). MMP-13 expression was high in Ethibond (R) group when compared with PDS (R) II (p<0.05). High IL-1 beta expression in tendons repaired with Ethibond (R) was found (p>0.05). Conclusions. Tendons repaired with PDS (R) II are found to have superior properties regarding extracellular matrix component synthesis-degradation, and inflammatory cytokine production at mRNA levels when compared to Vicryl (R) and Ethibond (R). These results can be a guide to surgeons regarding suture choice in Achilles tendon repairs.
Keywords: Achilles; PDS; mRNA; collagen; decorin; MMP-13; REPAIR; INJURY; RAT; STRENGTH